Disaster Preparedness Analysis At Intensive Health Centers In Toba Regency In 2020 - Pardede, Mangapul; EL- Matury, Herlina J.; Batubara, Saiful (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2021)
This study analyzes the level of disaster preparedness in inpatient health centers in Toba Regency. The variables studied were disaster potential, structural safety, non-structural safety, and functional aspects. The results showed that the preparedness scores for the Ajibata Inpatient Health Center and the Parsoburan Inpatient Health Center required both inpatient health centers to intervene in the near future because they still had risks when facing disasters. Meanwhile, the Laguboti Inpatient Health Center is considered capable of protecting human life and still functioning in the event of a disaster. The structural safety score of the Ajibata Inpatient Health Center reflects that the structural security is adequate for disaster events. Meanwhile, the Parsoburan Inpatient Health Center still has a risk for disaster events. The non-structural safety scores of the Ajibata and Laguboti Inpatient Health Centers both still have risks in dealing with disasters. The Parsoburan Inpatient Health Center is not ready to face a disaster. The value of the functional aspects of the three Inpatient Health Centers shows that the three Inpatient Health Centers are not functionally ready to face disaster events. It is recommended that the three Inpatient Health Centers should continue to improve disaster preparedness.